Strategi Pengembangan Usaha Budidaya Rumput Laut Di Desa Lalombi Kecamatan Banawa Selatan Kabupaten Dongala - Nurdin, Muh. Fahruddin; Laapo, Alimudin; Howara, Dafina (AGROTEKBIS, 2013)
This research aimed to develop the good strategy in the development of seaweed cultivation. The research was implemented in Lalombi Village, Sub District of South Banawa, Donggala Regency, Province of Central Sulawesi.  About 60 people are active as the seaweed farmers which 6 farmers is taken from respondent and 2 people from relevant agencies so overall there are 8 people as respondents with the determination of respondent were calculated using judgment sampling, the respondents chose the most right to provide information needed. Respondents are determined based on the assumption that they could still represent the population characteristics of seaweed farmers. Based on the results of the research identified from internal factors, there are five strengths and five weaknesses, and for the external environmental factors there are five chances and five threats. Combination value IFE is 2.76 and value of EFE is 2.25 in the IE matrix shows that the position of the business in V cells, the growth through horizontal integration, an activity to develop the business by way of utilizing land resources more leverage and increase value by be processed seaweed derived products. Strategy development of seaweed cultivation in the village lalombi is optimize production, provide counseling and gradually expand seaweed cultivation area.